La formación de futuros profesionales del derecho para trabajar con traductores e intérpretes: un estudio cualitativo - Alcalde Peñalver, Elena; Pajares Nievas, José Sergio (Lenguas Modernas, 2019)
Students of Law are well advised to gain an understanding of legal English for their legal career. Importantly, teaching units in legal English can also contribute to an awareness of the complex interface between translators and interpreters and the legal system. In this investigation, the potential of teaching activities to educate future lawyers in the intricacies of these professions is unlocked. An initial questionnaire with open-ended questions was administered to students studying for the Master’s Degree in Law and Legal Practice at the University of Burgos, Spain. The questionnaire explored knowledge of the profession of legal and sworn translators and interpreters. The results revealed low levels of familiarization with the translation profession among students and they did not even know about the regulations that govern their work. Different classroom activities were conducted to educate and inform future lawyers about the tasks and roles of these language professionals. By the end of the course, a qualitative change in students’ perceptions of the work of legal and sworn translators and interpreters was evident. The introduction of foreign language courses and comparative law in legal training with specific activities focused on legal and sworn translation and interpreting can therefore be of immense assistance in crystallizing an awareness of the role of specialized linguists in the legal profession.